A Comparative Study of the In Vitro Intestinal Permeability of Pinnatoxins and Portimine - Rachelle Lanceleur; Vincent Hort; Marion Peyrat; Denis Habauzit; Andrew I. Selwood; Valérie Fessard (Marine Drugs)
The pinnatoxins (PnTXs) and portimines, produced by Vulcanodinium rugosum, have been detected in several countries, raising concerns for human health. Although no human poisoning from these toxins has been reported so far, they have been shown to distribute throughout the rodent body after oral administration. Therefore, we investigated the impact of PnTX analogs (PnTX-A, -E, -F, -G, and -H) and portimine (8, 16, and 32 ng/mL) on intestinal barrier integrity and their oral bioavailability using human Caco-2 cell monolayers treated for 2, 6, and 24 h. Our results demonstrated that all of the toxins could impair barrier integrity after 24 h, with differences observed for PnTX-A, -E, and -F, as well as portimine, the most potent of all. While PnTX-A and -E exhibited poor permeability, the other PnTXs were more penetrative, with a Papp > 1.5 × 10−6 cm·s−1. Portimine was the only toxin displaying both a time- and concentration-dependent passage, likely involving a passive diffusion process. The experimental results were compared to predictions obtained by QSAR tools. Although only qualitative, our results suggest that some of these compounds may be more likely to be distributed throughout the body. Further in vivo studies are required to estimate oral bioavailability and potential public health concerns.